Developing Economies And International Investors : Do Investment Promotion Agencies Bring Them Together ? - Harding, Torfinn (The World Bank, 2007)
Many countries spend significant resources on investment promotion agencies in the hope of attracting inflows of foreign direct investment. Despite the importance of this question for public policy choices, little is known about the effectiveness of investment promotion efforts. This study uses newly collected data on national investment promotion agencies in 109 countries to examine the effects of investment promotion on foreign direct investment inflows. The empirical analysis follows two approaches. First, it tests whether sectors explicitly targeted by investment promotion agencies receive more foreign direct investment in the post-targeting period relative to the pre-targeting period and non-targeted sectors. Second, it examines whether the existence of an investment promotion agency is correlated with higher foreign direct investment inflows. Results from both approaches point to the same conclusion. Investment promotion efforts appear to increase foreign direct investment inflows to developing countries. Moreover, agency characteristics, such as the agency's legal status and reporting structure, affect the effectiveness of investment promotion. There is also evidence of diversion of foreign direct investment due to investment incentives offered by other countries in the same geographic region